The Effect Of Training And Work Motivation On The Performance Of Village Office Employees In Seginim District, South Bengkulu Regency - Ilhami, Mardhiyah Dwi; Bustam, Taufik; Prasetyo, Gegen (Penerbit Jurnal Indonesia, 2023)
This study aims to determine